Digestibily of Some Kind of Alternative Diets on Lesser Mouse Deer (Tragulus javanicus) - Farida, WR; Semiadi, G; Dahruddin, H (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2004)
Four female lesser mouse deer (Tragulus javanicus) were used in this study to observe their feed consumption and digestibility given alternative diets in captive.Â The results showed that 125g/head/day sweet potatoes supplementation in ration increased the consumption and digestibility of dry matter intake, ash, ether extract, and N-free extract. Supplementation of commercial concentrate in lesser mouse deerâs diet decreased the digestion of dry matter, ash, crude protein, and crude fiber. Animal Production 6(1): 17-22 (2004)Â Key Words: Digestibility, Consumption, Alternative Diets, Tragulus javanicus